Light guides based on terbium-doped borate glass - Michelle Grüne; Stefan Schweizer (Optical Materials: X, 2022)
Luminescent light guides on the basis of barium borate glass are studied. The light guides are optically-activated with different amounts of trivalent terbium ions. Absorption coefficient, photoluminescence quantum efficiency, as well as photoluminescence emission spectra from reference samples serve as input data for ray-tracing simulations. The simulations yield an optimum light guide length of approximately 50mm with the side faces of the light guide coated with a 100% reflecting mirror and a rough output face with Lambertian scattering characteristic. The input face is a half-transmitting mirror which is transmissive for the excitation wavelength of 378nm but reflective for the emission bands in the visible spectral range. For a light guide with a Tb3+ content of 1.77at.%, a luminance of more than 60cd/mm2 is predicted for an excitation power density of 1W/mm2.